Design and Review of Virtual Reality (VR) System for Treating Patients with Height and Darkness Phobia - Akbar Jafari; Ali Asghar Safae (Tehran University of Medical Sciences, 2020)
Background and Aim: Implementation of virtual reality systems in the field of health care has recently made significant progress. This article aims to examine a virtual reality-based system designed for patients with two types of phobia: darkness and height. Materials and Methods: The present paper is the result of a study conducted by searching valid scientific sources including Springer, PubMed and Science Direct(Elsevier), and observing and examining similar virtual reality systems. According to the performed studies, patients enter the virtual reality environment based on their phobia and physician opinion. To assess the effect of phobia, a series of questionnaires are used before and after the test; and using these questionnaires, physicians can evaluate the extent of their patientschr('39') recovery. Results: One of the ways to treat phobia is to put the patient in real environment; but in terms of cost and feasibility, it is not possible to provide the environment for physicians and patients in many cases. However, by using virtual reality technology and in the system designed in this paper, psychiatrists can implement real environments as virtual reality in front of the patientchr('39')s eyes. Conclusion: In the system presented in this study, the existence of several diverse and appropriate virtual reality environments for the care and treatment of patients with darkness and height phobia is one of its distinct points because in many studies only a fixed environment is used for patients.